PENGARUH LATIHAN MULTIBALL TERHADAP KETERAMPILAN PUKULAN BACKHAND DRIVE ATLET PUTRA TENIS MEJA PUSAT PENDIDIKAN DAN PELATIHAN PELAJAR (PPLP) RIAU - Zuilendra, Rahmad; ', Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is the lack of backhand drive skill of male athletes in Student Education and Training Center (PPLP) Riau. Based on these problems, the researchers conducted multiball training. This research aims to determine whether there is any effect of multiball training on the backhand drive skill of male athletes in Student Education and Training Center (PPLP) Riau. At the time of doing backhand drive skill got maximum results. The form of this research is treatment trial (experimental) research, with the population of table tennis male athletes in Student Education and Training Center (PPLP) Riau, the data in this research consisted of a population of 6 people. The instrument performed in this research is a backboard test, which aims to measure how many athletes can hit backhand drives. After that, the data were processed using statistics, the normality was tested using the lilifors test at a significant level of α (0.05). The hypothesis proposed is there is indeed an effect of multiball training towards backhand drive skill. Based on the statistical data analysis, there is an average pre-test of 34.83 and an average post-test of 38.5, then the data is normal with an increase of 3.67. Based on t test, analysis yielded Tcount is equal to 8,73 and Ttable is equal to 2.015, meaning Tcount > T table. Thus, there is an effect of multiball training on the backhand drive skill of table tennis male athletes in Student Education and Training Center (PPLP) Riau.Keywords: Multiball , Backhand Drive Skill